Islam and Local Traditions: The Study of the Thinkings of Abdurrahman Wahid (1940-2009) and Khalil Abdul Karim (1930-2002) an Indonesian and an Egyptian Perspective - Siti Mahmudah (Universitas Islam Negeri Sunan Kalijaga, 2018)
Islam and local tradition had already coexisted peacefully since Islam was revealed by Allah for the first time through the Gabriel Angel to the Prophet Muhammad in Mecca on 610 M. According to Mohammed A. Muqtedar Khan, there were traditions and ethics of Islam, based on the origin of the the sharia misunderstood by the most Muslims until now. Abdurrahman Wahid (Gus Dur) with his theory of the Pribumisasi Islam and Khalil Abdul Karim with his theory about the early existence of the Islam and sharia has been revealed among the pre-Islamic Arab tradition as the blueprint for Islam and the sharia in this era. Both of these theories are those of the continuation of Islam for all times and places. For the first time, Islam and the sharia gave high appreciation and respect to the Arab tradition and had even enshrined Arab traditions that are considered good and maslahat for humanitarian life remains entrenched to the teachings of Islam and enshrined in the Qur'an. Both of these theories can be used as the basis for rejecting the discovery of Timothy Daniel about